Epidemiology of dengue/dengue hemorrhagic fever in Malaysia--a retrospective epidemiological study 1973-1987. Part I: Dengue hemorrhagic fever (DHF) - Shekhar, K.C.; Huat, O.L. (SAGE Publications, 1992)
Dengue hemorrhagic fever (DHF), though endemic in the sixties, emerged as a major public health problem in Malaysia from 1973 onwards. The incidence rate of DHF which was 10.1 per 100,000 in 1973 has fallen down to 1.9 per 100,000 in 1987 with a mean case fatality rate of 6.4 per 100 persons. The Chinese appear to be more prone to DHF with the highest mean morbidity rate of 5.5 per 100,000 and case fatality rate of 6.1%. The incidence of DHF is higher in the males with a higher case fatality rate in females. Male Chinese appear to be mainly affected. The overall age-specific incidence rate is highest in two age groups, viz. 5-9 years and 10-19 years of age with a mean morbidity rate of 4.9 cases per 100,000. The mean age-specific case fatality rate was highest in the 0-4 years age group. Dengue hemorrhagic fever is predominantly an urban disease in Malaysia with a mean incidence rate of 5.3 cases per 100,000 as opposed to 1.2 cases per 100,000 being reported from rural areas. The mean overall incidence of deaths in the urban area is 0.5 compared to 0.1 per 100,000 for rural areas. There is a marked seasonal correlation between DHF cases and rainfall, with a peak in August. While all four serotypes of dengue viruses are found in Malaysia, Den 2 appears to be isolated with greater frequency during all the epidemics.